Estimating Poland's Potential Output : A Production Function Approach - Epstein, Natan (IMF Working Papers; Working Paper ;, 2010)
The paper develops a methodology based on the production-function approach to estimate potential output of the Polish economy. The paper concentrates on obtaining a robust estimate of the labor input by deriving Poland's natural rate of unemployment. The estimated unemployment gap is found to track well pressures on resource constraints. Moreover, the overall results show that, prior to the recent global financial crisis, Poland's output and employment were both growing above potential. The production function is also used to derive medium-term projections of the output gap. According to our methodology, in the aftermath of the global crisis, Poland is not expected to experience a sizable and persistent negative output gap.